The China alternative : changing regional order in the Pacific Islands - Smith, Graeme Kevin; Wesley-Smith, Terence (Pacific series., 2021)
The China Alternative includes chapters on growing great power competition in the region, as well as the response to China's rise by the US and its Western allies and the island countries themselves. Other chapters examine key dimensions of China's Pacific engagement, including Beijing's programs of aid and diplomacy, as well as the massive investments of the Belt and Road Initiative. The impact of China's rivalry for recognition with Taiwan is examined, and several chapters analyse Chinese communities in the Pacific, and their relationships with local societies. The China Alternative provides ample material for informed judgements about the ability of island leaders to maintain their agency in the changing regional order, as well as other issues of significance to the peoples of the region.